Quick-setting hot-melt marking coating and preparation method thereof
By combining modified epoxy resin and rare earth-doped fluorescent nanomaterials, a quick-setting hot-melt road marking paint was prepared, which solved the problems of existing paints in wear resistance, luminescence time, drying speed and construction efficiency, and achieved high adhesion, long life and all-weather visibility.
Patent Information
- Application Number
- CN202511048651.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-09-12
AI Technical Summary
Existing thermoplastic road marking paints fade under long-term sunlight, have a short luminous time, dry slowly, crack at low temperatures, have poor stain resistance, lack of reflective durability, low construction efficiency, and are prone to agglomeration during construction.
Using modified epoxy resin, self-healing microcapsules, rare earth doped fluorescent nano wear-resistant materials and hollow glass microspheres as components, a fast-setting hot-melt road marking paint with self-healing function is prepared through the copolymerization of modified silane coupling agent and acrylate, which improves adhesion and wear resistance, and achieves continuous luminescence through rare earth doped fluorescent materials.
It improves the wear resistance, adhesion and service life of the coating, ensures all-weather visibility, has good damage repair ability and anti-fouling and anti-scaling properties, and improves construction efficiency and reflective performance.
Smart Images

Figure BDA0005522477620000201
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to a quick-setting hot-melt road marking coating and a preparation method thereof. Background Art
[0002] Road markings are primarily applied to road surfaces to regulate the passage of vehicles and pedestrians, ensuring each follows its own lane without interfering with the other, and ensuring safe and smooth traffic. Because they are subject to the elements, such as sun, rain, wind, snow, and ice, as well as the impact and wear of vehicles, they are subject to stringent performance requirements. Firstly, they must have a fast drying time and be easy to operate to minimize traffic disruptions. Secondly, they must have strong reflectivity, vibrant colors, and high light reflectivity to ensure good visibility both day and night. Thirdly, they must be skid-resistant and wear-resistant to ensure driving safety and a long service life.
[0003] Hot-melt road marking paints on the market often use titanium dioxide as a pigment. However, titanium dioxide will fade and become unclear under long-term sunlight exposure. In addition, construction workers have found that the raw materials are prone to agglomeration during use, which is inconvenient to use. At the same time, it has been found that some night-luminous paints on the market also contain calcium carbonate, titanium dioxide, disodium ethylenediaminetetraacetic acid, silicon dioxide and other ingredients, but their preparation process is to mix them directly, and the paint obtained by direct mixing only shows the basic properties of its materials. During actual use, construction workers will encounter short luminescence time and low luminescence brightness. The phenomenon of no luminescence occurs after 2-3 days of use, and fluorescence quenching occurs. Especially under high temperature conditions, the fluorescence quenching time is even shorter, and it cannot serve as a warning at night. At the same time, traditional products also have bottlenecks such as slow drying speed, low-temperature cracking, poor anti-fouling properties, insufficient reflective durability, and low construction efficiency.
[0004] Therefore, the prior art needs further improvement. Summary of the Invention
[0005] The purpose of the present invention is to propose a quick-setting hot-melt road marking paint and a preparation method thereof, which has good wear resistance, mechanical properties and adhesion, is anti-shedding, has a long service life, continuously luminous, improves all-weather visibility, has good damage repair effect, good anti-fouling and anti-scaling properties, and has broad application prospects.
[0006] The technical solution of the present invention is achieved as follows:
[0007] The present invention provides a quick-setting hot-melt road marking paint, which is prepared from the following raw materials in parts by weight: 100-110 parts of modified epoxy resin, 5-10 parts of curing agent, 5-10 parts of titanium dioxide, 3-5 parts of self-repairing microcapsules, 2-4 parts of basalt fiber, 4-6 parts of rare earth-doped fluorescent nano-wear-resistant material, 3-5 parts of hollow glass microspheres, and 0.1-0.2 parts of rheological agent.
[0008] As a further improvement of the present invention, the preparation method of the modified epoxy resin is as follows:
[0009] S1. The epoxy resin was added to ethanol, a composite silane coupling agent was added, the reaction was heated with stirring, and the solvent was removed under reduced pressure to obtain a silane coupling agent-modified epoxy resin;
[0010] S2. Add the silane coupling agent-modified epoxy resin to acetone, add ethyl acrylate, methacrylic acid, and butyl acrylate, heat and stir to mix, add an initiator under the protection of an inert gas, keep warm and stir to react, add water to precipitate, filter, wash, and dry to obtain a modified epoxy resin.
[0011] As a further improvement of the present invention, the epoxy resin in step S1 is E51, the mass ratio of the epoxy resin to the composite silane coupling agent is 15-20:2-3, the composite silane coupling agent includes KH570 and KH602 in a mass ratio of 3-5:7-10, the temperature of the heating and stirring reaction is 40-50°C, and the time is 3-5 hours; in step S2, the mass ratio of the silane coupling agent-modified epoxy resin, ethyl acrylate, methacrylic acid, butyl acrylate, and initiator is 12-15:2-4:1-3:2-3:0.01-0.015, the initiator is selected from at least one of sodium persulfate, potassium persulfate, and ammonium persulfate, the heating temperature is 50-60°C, and the insulation and stirring reaction time is 4-6 hours.
[0012] As a further improvement of the present invention, the preparation method of the self-repairing microcapsules is as follows:
[0013] T1. The vapor phase SiO2 was added to ethanol, perfluorooctyl triethoxysilane and water were added, and the reaction was stirred to obtain SiO2-perfluorooctyl triethoxysilane emulsifier;
[0014] T2. The vapor phase SiO2 was added to ethanol, dithiothiadiazole was added, silane coupling agent KH580 and water were added, and the reaction was stirred to obtain SiO2-dithiothiadiazole emulsifier;
[0015] T3. The formaldehyde solution and triethanolamine were mixed, urea was added, the reaction was heated with stirring, melamine was added, and the reaction was kept warm to obtain a modified urea-formaldehyde resin prepolymer;
[0016] T4. Evenly mix lauric acid, water, emulsifier, SiO2-perfluorooctyltriethoxysilane emulsifier, and SiO2-dimercaptothiadiazole emulsifier, add modified urea-formaldehyde resin prepolymer, adjust the pH value of the solution, heat and stir to react, and dry to obtain self-healing microcapsules.
[0017] As a further improvement of the present invention, the mass ratio of the gaseous SiO2 and perfluorooctyltriethoxysilane in step T1 is 10:3-5, and the stirring reaction time is 10-12h; the mass ratio of the gaseous SiO2, dithiothiadiazole, and silane coupling agent KH580 in step T2 is 10:2-4:1-2, and the stirring reaction time is 10-12h; the mass ratio of the formaldehyde solution, triethanolamine, urea, and melamine in step T3 is 10:2-3:7-8:2-3, and the temperature of the heating and stirring reaction is 10:1-2. The temperature of the reaction mixture is 80-90°C, the time is 0.5-1h, and the insulation reaction time is 0.5-1.5h; the mass ratio of lauric acid, water, emulsifier, SiO2-perfluorooctyltriethoxysilane emulsifier, SiO2-dimercaptothiadiazole emulsifier and modified urea-formaldehyde resin prepolymer in step T4 is 1-2:0.1-0.3:2-3:1-2:10, the pH value of the solution is adjusted to 2-4, the temperature of the heating and stirring reaction is 40-50°C, the time is 2-4h, and the emulsifier is OP-10 or Tween-85.
[0018] As a further improvement of the present invention, the preparation method of the rare earth doped fluorescent nano wear-resistant material is as follows:
[0019] U1. Preparation of formaldehyde-melamine resin microspheres: Formaldehyde solution and water are uniformly mixed, melamine is added, the pH of the solution is adjusted, the reaction is stirred, a metal salt is added, the reaction is continued with stirring, centrifugation is performed, washing is performed, and drying is performed to obtain formaldehyde-melamine resin microspheres;
[0020] U2. Silicon oxide coating: Formaldehyde - melamine resin microspheres were added to ethanol, alkyl orthosilicate was added, stirred and mixed, ammonia was added dropwise to adjust the pH of the solution, heated and stirred, centrifuged, washed, and dried to obtain silicon oxide-coated formaldehyde - melamine resin microspheres;
[0021] U3. Preparation of SiO2 / carbon nanotube hollow microspheres: Silicon oxide-coated formaldehyde-melamine resin microspheres were added to water, followed by iron salt, stirred, centrifuged, washed, dried, and calcined to produce SiO2 / carbon nanotube hollow microspheres.
[0022] Preparation of CaF2@SiO2 / carbon nanotube hollow microspheres: SiO2 / carbon nanotube hollow microspheres were added to water, followed by disodium EDTA, and stirred for reaction. Calcium salt was added and stirred for adsorption, followed by sodium fluoride. The mixture was hydrothermally reacted, centrifuged, washed, and dried to obtain CaF2@SiO2 / carbon nanotube hollow microspheres.
[0023] U5. Preparation of modified CaF2@SiO2 / carbon nanotube hollow microspheres: CaF2@SiO2 / carbon nanotube hollow microspheres were added to a Tris-HCl solution, tannic acid was added, the reaction was heated with stirring, centrifuged, washed, and dried to obtain modified CaF2@SiO2 / carbon nanotube hollow microspheres;
[0024] U6. Preparation of rare earth-doped fluorescent nano-wear-resistant material: Modified CaF2@SiO2 / carbon nanotube hollow microspheres were added to water, cerium chloride and yttrium nitrate were added, stirred, centrifuged, washed, and dried to obtain rare earth-doped fluorescent nano-wear-resistant material.
[0025] As a further improvement of the present invention, in step U1, the mass ratio of the formaldehyde solution, melamine, and metal salt is 8-12:2-3:0.1-0.2, the metal salt is cobalt chloride, the pH value of the solution is adjusted to 5-5.5, and the stirring reaction is carried out for 20-30 minutes; in step U2, the mass ratio of the formaldehyde-melamine resin microspheres and alkyl orthosilicate is 10:5-7, the alkyl orthosilicate is methyl orthosilicate or ethyl orthosilicate, the pH value of the solution is adjusted to 9-10 by adding ammonia water, the temperature of the heating and stirring reaction is 40-50°C, and the time is 6-8 hours; in step U3, the mass ratio of the silicon oxide-coated formaldehyde-melamine resin microspheres and iron salt is 100:2-3, the stirring reaction time is 20-40 minutes, and the calcination temperature is 900-950°C, and the time is 0.5-1.5 hours.
[0026] As a further improvement of the present invention, the mass ratio of SiO2 / carbon nanotube hollow microspheres, disodium EDTA, calcium salt, and sodium fluoride in step U4 is 10:1-2:3-5:5-7, the temperature of the hydrothermal reaction is 120-140°C, and the time is 10-20h; the mass ratio of CaF2@SiO2 / carbon nanotube hollow microspheres and tannic acid in step U5 is 10:2-3, the temperature of the heating and stirring reaction is 45-55°C, and the time is 3-5h; the mass ratio of modified CaF2@SiO2 / carbon nanotube hollow microspheres, cerium chloride, and yttrium nitrate in step U6 is 10:1-2:0.6-1.5, and the stirring reaction time is 1-2h.
[0027] As a further improvement of the present invention, the curing agent is triethylenediamine or tetraethylenetriamine; and the rheological agent is rheological agent BYK-R-605.
[0028] The present invention further protects a method for preparing the above-mentioned quick-setting hot-melt road marking paint, comprising the following steps:
[0029] The modified epoxy resin, titanium dioxide, self-repairing microcapsules, basalt fiber, rare earth doped fluorescent nano wear-resistant material and hollow glass microbeads are mixed evenly, a rheological agent is added, stirred and mixed, and finally a curing agent is added and the material is discharged to obtain a fast-setting hot-melt road marking paint.
[0030] The present invention has the following beneficial effects:
[0031] The present invention prepares a modified epoxy resin. Epoxy resin E51 is modified by using a silane coupling agent with a double bond and a silane coupling agent with an amino group, so that the epoxy resin can be copolymerized and modified with an acrylic acid (ester) monomer. The modified epoxy resin greatly improves the adhesion of the resin, reduces the risk of delamination and shedding of the coating after curing, improves its durability, and extends its service life. At the same time, the amino group and acrylic acid (ester) structure have good compatibility with other additives added thereto, greatly improving the dispersibility of the additives and preventing coagulation from affecting the use of the coating.
[0032] The present invention prepares a self-repairing microcapsule by coupling gas-phase SiO2 and perfluorooctyltriethoxysilane to obtain SiO2-perfluorooctyltriethoxysilane emulsifier. At the same time, gas-phase SiO2 and dithiothiadiazole and silane coupling agent KH580 are coupled to obtain SiO2-dithiothiadiazole emulsifier (thiol and thiol can react). These two emulsifiers can play a good emulsifying role on the one hand, and further prepare self-repairing microcapsules with polyurea resin, which improves the super-hydrophobicity and scale inhibition performance of the coating, improves the corrosion resistance, and the fluorine-containing layer can be used as a shielding layer to prevent water penetration, reduce the contact area between water droplets and the coating surface, and induce water droplets containing pollutants to leave. When the coating is corroded or damaged, the microcapsule releases dithiothiadiazole, which contains nitrogen and sulfur heterocycles in its structure and can chelate with metal ions. The S and N heteroatoms have large electrophilic indexes and are easy to react with metal empty orbitals to form coordination bonds. They are tightly adsorbed on the surface to form a protective film, slowing down the occurrence of surface corrosion reactions. The prepared self-healing microcapsules are added to the coating. When scratches appear on the coating, the microcapsules in the surrounding coating rupture, and the released repair agent can quickly fill the cracks, thereby re-forming a new protective layer at the scratches. It also plays an anti-corrosion role. The self-healing microcapsules and basalt fibers are evenly dispersed in the coating. The fibers bridge the cracks and trigger the rupture of the microcapsules, releasing the repair agent to fill the damaged area, while the fibers enhance the mechanical properties.
[0033] The present invention prepares a rare earth doped fluorescent nano wear-resistant material, which uses formaldehyde-melamine resin microspheres as the core and is coated with a silicon dioxide layer on the surface, thereby improving the wear resistance and mechanical properties of the coating. During the calcination process, NH3 and CO gases generated by the decomposition of the formaldehyde-melamine resin microspheres can serve as reducing gases and carbon sources to reduce iron ions, and promote the deposition of carbon nanotubes through autocatalytic reactions, thereby forming hollow microspheres. The hollow structure improves the coating's resistance to external environmental factors such as ultraviolet rays, oxygen, and water vapor, delays the aging and corrosion rate of the coating film, prolongs the service life of the coating, and also improves the coating's mechanical properties and hydrophobicity. The surface is loaded with CaF2 nanocrystals, which is a good luminescent material. After further loading rare earth elements, in the CaF2 type rare earth doped fluorescent nanomaterial, the F in the matrix - Ions can act as bridges to transfer energy to rare earth ions, thereby activating their luminescence. Rare earth ions have a unique 4f electron layer structure, and their luminescence mainly comes from the transition of 4f electrons. They have a long fluorescence lifetime, improve luminescence performance, absorb light energy during the day, and continue to emit light at night, improving all-weather visibility.
[0034] The quick-setting hot-melt road marking paint prepared by the present invention has good wear resistance, mechanical properties and adhesion, is anti-shedding, has a long service life, continuously emits light, improves all-weather visibility, has good damage repair effect, and has good anti-fouling and anti-scaling properties, and has broad application prospects. DETAILED DESCRIPTION
[0035] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0036] Preparation Example 1 Preparation of modified epoxy resin
[0037] Here’s how:
[0038] S1. 15 g of epoxy resin E51 was added to 300 mL of ethanol, 2 g of a composite silane coupling agent was added, the mixture was heated to 40 ° C, stirred for 3 h, and the solvent was removed under reduced pressure to obtain a silane coupling agent-modified epoxy resin;
[0039] The composite silane coupling agent includes KH570 and KH602 in a mass ratio of 3:7;
[0040] S2. Add 12 g of silane coupling agent-modified epoxy resin to 300 mL of acetone, add 2 g of ethyl acrylate, 1 g of methacrylic acid, and 2 g of butyl acrylate, heat to 50°C, stir and mix, add 0.01 g of potassium persulfate under nitrogen protection, keep warm and stir to react for 4 hours, add water to precipitate, filter, wash, and dry to obtain modified epoxy resin.
[0041] Preparation Example 2 Preparation of modified epoxy resin
[0042] Here’s how:
[0043] S1. 20 g of epoxy resin E51 was added to 300 mL of ethanol, 3 g of a composite silane coupling agent was added, heated to 50 ° C, stirred for 5 h, and the solvent was removed under reduced pressure to obtain a silane coupling agent-modified epoxy resin;
[0044] The composite silane coupling agent includes KH570 and KH602 in a mass ratio of 5:10;
[0045] S2. Add 15 g of silane coupling agent-modified epoxy resin to 300 mL of acetone, add 4 g of ethyl acrylate, 3 g of methacrylic acid, and 3 g of butyl acrylate, heat to 60°C, stir and mix, add 0.015 g of sodium persulfate under nitrogen protection, keep warm and stir to react for 6 hours, add water to precipitate, filter, wash, and dry to obtain modified epoxy resin.
[0046] Preparation Example 3 Preparation of modified epoxy resin
[0047] Here’s how:
[0048] S1. 17 g of epoxy resin E51 was added to 300 mL of ethanol, 2.5 g of a composite silane coupling agent was added, heated to 45 ° C, stirred for 4 h, and the solvent was removed under reduced pressure to obtain a silane coupling agent-modified epoxy resin;
[0049] The composite silane coupling agent includes KH570 and KH602 in a mass ratio of 4:9;
[0050] S2. Add 13 g of silane coupling agent-modified epoxy resin to 300 mL of acetone, add 3 g of ethyl acrylate, 2 g of methacrylic acid, and 2.5 g of butyl acrylate, heat to 55°C, stir and mix, add 0.012 g of ammonium persulfate under nitrogen protection, keep warm and stir to react for 5 hours, add water to precipitate, filter, wash, and dry to obtain modified epoxy resin.
[0051] Comparative Preparation Example 1
[0052] Compared with Preparation Example 3, the difference is that step S1 is not performed.
[0053] The details are as follows:
[0054] 13 g of epoxy resin E51 was added to 300 mL of acetone, and 3 g of ethyl acrylate, 2 g of methacrylic acid, and 2.5 g of butyl acrylate were added. The mixture was heated to 55°C and stirred. Under nitrogen protection, 0.012 g of ammonium persulfate was added. The mixture was stirred and reacted for 5 h. Water was added for precipitation, and the mixture was filtered, washed, and dried to obtain a modified epoxy resin.
[0055] Comparative Preparation Example 2
[0056] Compared with Preparation Example 3, the difference is that step S2 is not performed.
[0057] The details are as follows:
[0058] 17 g of epoxy resin E51 was added to 300 mL of ethanol, and 2.5 g of a composite silane coupling agent was added. The mixture was heated to 45°C and stirred for 4 h. The solvent was removed under reduced pressure to obtain a modified epoxy resin.
[0059] The composite silane coupling agent includes KH570 and KH602 in a mass ratio of 4:9.
[0060] Preparation Example 4 Preparation of self-repairing microcapsules
[0061] Here’s how:
[0062] T1. 1 g of vapor-phase SiO2 was added to 100 mL of ethanol, 0.3 g of perfluorooctyltriethoxysilane and 1 mL of water were added, and the reaction was stirred for 10 h to obtain SiO2-perfluorooctyltriethoxysilane emulsifier;
[0063] T2. 1 g of vapor-phase SiO2 was added to 100 mL of ethanol, 0.2 g of dithiothiadiazole, 0.1 g of silane coupling agent KH580 and 5 mL of water were added, and the reaction was stirred for 10 h to obtain a SiO2-dithiothiadiazole emulsifier;
[0064] T3. 10 g of formaldehyde solution and 2 g of triethanolamine were mixed for 30 min, 7 g of urea was added, the pH of the solution was adjusted to 5.5, the solution was heated to 80 ° C, stirred for 0.5 h, 2 g of melamine was added, and the reaction was kept at this temperature for 0.5 h to obtain a modified urea-formaldehyde resin prepolymer;
[0065] T4. Mix 1 g of lauric acid, 100 mL of water, 0.1 g of OP-10, 2 g of SiO2-perfluorooctyltriethoxysilane emulsifier, and 1 g of SiO2-dimercaptothiadiazole emulsifier. Add 10 g of modified urea-formaldehyde resin prepolymer. Adjust the pH of the solution to 2. Heat to 40°C, stir the reaction for 2 h, and dry to obtain self-healing microcapsules.
[0066] Preparation Example 5 Preparation of self-repairing microcapsules
[0067] Here’s how:
[0068] T1. 1 g of vapor-phase SiO2 was added to 100 mL of ethanol, 0.5 g of perfluorooctyltriethoxysilane and 1 mL of water were added, and the reaction was stirred for 12 h to obtain SiO2-perfluorooctyltriethoxysilane emulsifier;
[0069] T2. 1 g of vapor-phase SiO2 was added to 100 mL of ethanol, 0.4 g of dithiothiadiazole, -0.2 g of silane coupling agent KH580 and 5 mL of water were added, and the reaction was stirred for 12 h to obtain SiO2-dithiothiadiazole emulsifier;
[0070] T3. 10 g of formaldehyde solution and 3 g of triethanolamine were mixed for 30 min, 8 g of urea was added, the pH of the solution was adjusted to 5.5, the solution was heated to 90 ° C, stirred for 1 h, 3 g of melamine was added, and the reaction was kept at this temperature for 1.5 h to obtain a modified urea-formaldehyde resin prepolymer;
[0071] T4. Mix 2 g of lauric acid, 100 mL of water, 0.3 g of Tween-85, 3 g of SiO2-perfluorooctyltriethoxysilane emulsifier, and 2 g of SiO2-dimercaptothiadiazole emulsifier. Add 10 g of modified urea-formaldehyde resin prepolymer, adjust the solution pH to 4, heat to 50°C, stir and react for 4 h, and dry to obtain self-healing microcapsules.
[0072] Preparation Example 6 Preparation of self-repairing microcapsules
[0073] Here’s how:
[0074] T1. 1 g of vapor-phase SiO2 was added to 100 mL of ethanol, 0.4 g of perfluorooctyltriethoxysilane and 1 mL of water were added, and the reaction was stirred for 11 h to obtain SiO2-perfluorooctyltriethoxysilane emulsifier;
[0075] T2. 1 g of vapor-phase SiO2 was added to 100 mL of ethanol, 0.3 g of dithiothiadiazole, 0.15 g of silane coupling agent KH580 and 5 mL of water were added, and the reaction was stirred for 11 h to obtain a SiO2-dithiothiadiazole emulsifier;
[0076] T3. 10 g of formaldehyde solution and 2.5 g of triethanolamine were mixed for 30 min, 7.5 g of urea was added, the pH of the solution was adjusted to 5.5, the solution was heated to 85°C, stirred for 1 h, 2.5 g of melamine was added, and the mixture was kept at this temperature for 1 h to obtain a modified urea-formaldehyde resin prepolymer;
[0077] T4. Mix 1.5 g of lauric acid, 100 mL of water, 0.2 g of OP-10, 2.5 g of SiO2-perfluorooctyltriethoxysilane emulsifier, and 1.5 g of SiO2-dimercaptothiadiazole emulsifier. Add 10 g of modified urea-formaldehyde resin prepolymer, adjust the pH of the solution to 3, heat to 45°C, stir the reaction for 3 h, and dry to obtain self-healing microcapsules.
[0078] Comparative Preparation Example 3
[0079] Compared with Preparation Example 6, the difference is that SiO2-perfluorooctyltriethoxysilane emulsifier is not added in step T4.
[0080] The details are as follows:
[0081] T4. Mix 1.5 g of lauric acid, 100 mL of water, 0.2 g of OP-10, and 4 g of SiO2-dimercaptothiadiazole emulsifier. Add 10 g of modified urea-formaldehyde resin prepolymer. Adjust the pH of the solution to 3. Heat to 45°C, stir the mixture for 3 h, and dry it to obtain self-healing microcapsules.
[0082] Comparative Preparation Example 4
[0083] Compared with Preparation Example 6, the difference is that no SiO2-dimercaptothiadiazole emulsifier is added in step T4.
[0084] The details are as follows:
[0085] T4. Mix 1.5 g of lauric acid, 100 mL of water, 0.2 g of OP-10, and 4 g of SiO2-perfluorooctyltriethoxysilane emulsifier. Add 10 g of modified urea-formaldehyde resin prepolymer. Adjust the pH of the solution to 3. Heat to 45°C, stir and react for 3 h, and dry to obtain self-healing microcapsules.
[0086] Comparative Preparation Example 5
[0087] Compared with Preparation Example 6, the difference is that the SiO2-perfluorooctyltriethoxysilane emulsifier and the SiO2-dimercaptothiadiazole emulsifier are not added in step T4.
[0088] The details are as follows:
[0089] T4. Mix 1.5 g of lauric acid, 100 mL of water, and 0.2 g of OP-10, add 10 g of modified urea-formaldehyde resin prepolymer, adjust the pH of the solution to 3, heat to 45°C, stir and react for 3 h, and dry to produce self-healing microcapsules.
[0090] Preparation Example 7 Preparation of rare earth doped fluorescent nano wear-resistant material
[0091] Here’s how:
[0092] U1. Preparation of formaldehyde-melamine resin microspheres: 8 g of formaldehyde solution and 200 mL of water were mixed, 2 g of melamine was added, the pH of the solution was adjusted to 5, and the reaction was stirred for 20 min. 0.1 g of cobalt chloride was added and the reaction was continued with stirring for 20 min. The mixture was centrifuged, washed, and dried to obtain formaldehyde-melamine resin microspheres.
[0093] U2. Silicon oxide coating: 10 g of formaldehyde-melamine resin microspheres were added to 200 mL of ethanol, 5 g of methyl orthosilicate was added, and the mixture was stirred until uniform. Ammonia was added dropwise to adjust the solution to pH 9. The mixture was heated to 40°C and stirred for 6 h. The mixture was centrifuged, washed, and dried to obtain silicon oxide-coated formaldehyde-melamine resin microspheres.
[0094] Preparation of SiO2 / carbon nanotube hollow microspheres: 10 g of silicon oxide-coated formaldehyde-melamine resin microspheres were added to 150 mL of water, along with 0.1 g of ferric chloride. The mixture was stirred for 20 min, centrifuged, washed, dried, and calcined at 900°C under argon for 0.5 h to obtain SiO2 / carbon nanotube hollow microspheres.
[0095] Preparation of U4.CaF2@SiO2 / carbon nanotube hollow microspheres: 10 g of SiO2 / carbon nanotube hollow microspheres were added to 200 mL of water, followed by 1 g of disodium EDTA. The mixture was stirred for 30 minutes. 3 g of calcium nitrate was added and adsorbed with stirring for 30 minutes. Then, 5 g of sodium fluoride was added. The mixture was hydrothermally reacted at 120°C for 10 hours. The mixture was centrifuged, washed, and dried to obtain CaF2@SiO2 / carbon nanotube hollow microspheres.
[0096] U5. Preparation of modified CaF2@SiO2 / carbon nanotube hollow microspheres: 10 g of CaF2@SiO2 / carbon nanotube hollow microspheres were added to 20 mL of Tris-HCl solution (pH 9), 2 g of tannic acid was added, and the mixture was heated to 45°C and stirred for 3 h. The mixture was then centrifuged, washed, and dried to obtain modified CaF2@SiO2 / carbon nanotube hollow microspheres.
[0097] U6. Preparation of rare earth-doped fluorescent nano-wear-resistant material: Add 10 g of modified CaF2@SiO2 / carbon nanotube hollow microspheres to 150 mL of water, add 1 g of cerium chloride and 0.6 g of yttrium nitrate, stir and react for 1 h, centrifuge, wash, and dry to obtain rare earth-doped fluorescent nano-wear-resistant material.
[0098] Preparation Example 8 Preparation of rare earth doped fluorescent nano wear-resistant material
[0099] Here’s how:
[0100] U1. Preparation of formaldehyde-melamine resin microspheres: 12 g of formaldehyde solution and 200 mL of water were mixed, 3 g of melamine was added, the pH of the solution was adjusted to 5.5, and the reaction was stirred for 30 min. 0.2 g of cobalt chloride was added and the reaction was continued with stirring for 30 min. The mixture was centrifuged, washed, and dried to obtain formaldehyde-melamine resin microspheres.
[0101] U2. Silicon oxide coating: 10 g of formaldehyde-melamine resin microspheres were added to 200 mL of ethanol, 7 g of tetraethyl orthosilicate was added, and the mixture was stirred until uniform. Ammonia was added dropwise to adjust the pH of the solution to 10. The mixture was heated to 50°C and stirred for 8 h. The mixture was centrifuged, washed, and dried to obtain silicon oxide-coated formaldehyde-melamine resin microspheres.
[0102] U3. Preparation of SiO2 / carbon nanotube hollow microspheres: 10 g of silicon oxide-coated formaldehyde-melamine resin microspheres were added to 150 mL of water, along with 0.2 g of ferric chloride. The mixture was stirred for 40 min, centrifuged, washed, dried, and calcined at 950°C under argon for 1.5 h to obtain SiO2 / carbon nanotube hollow microspheres.
[0103] Preparation of U4.CaF2@SiO2 / carbon nanotube hollow microspheres: 10 g of SiO2 / carbon nanotube hollow microspheres were added to 200 mL of water, followed by 2 g of disodium EDTA. The mixture was stirred for 30 min. 5 g of calcium nitrate was added and adsorbed with stirring for 30 min. Then, 7 g of sodium fluoride was added. The mixture was hydrothermally reacted at 140°C for 20 h. The mixture was centrifuged, washed, and dried to obtain CaF2@SiO2 / carbon nanotube hollow microspheres.
[0104] Preparation of modified CaF2@SiO2 / carbon nanotube hollow microspheres: 10 g of CaF2@SiO2 / carbon nanotube hollow microspheres were added to 20 mL of Tris-HCl solution (pH 9), 3 g of tannic acid was added, and the mixture was heated to 55°C and stirred for 5 h. The mixture was then centrifuged, washed, and dried to obtain modified CaF2@SiO2 / carbon nanotube hollow microspheres.
[0105] U6. Preparation of rare earth-doped fluorescent nano-wear-resistant material: 10 g of modified CaF2@SiO2 / carbon nanotube hollow microspheres were added to 150 mL of water, along with 2 g of cerium chloride and 1.5 g of yttrium nitrate. The mixture was stirred for 2 h, centrifuged, washed, and dried to obtain the rare earth-doped fluorescent nano-wear-resistant material.
[0106] Preparation Example 9 Preparation of rare earth doped fluorescent nano wear-resistant material
[0107] Here’s how:
[0108] U1. Preparation of formaldehyde-melamine resin microspheres: 10 g of formaldehyde solution and 200 mL of water were mixed, 2.5 g of melamine was added, the pH of the solution was adjusted to 5.2, and the reaction was stirred for 25 minutes. 0.15 g of cobalt chloride was added and the reaction was continued with stirring for 25 minutes. The mixture was centrifuged, washed, and dried to obtain formaldehyde-melamine resin microspheres.
[0109] U2. Silicon oxide coating: 10 g of formaldehyde-melamine resin microspheres were added to 200 mL of ethanol, followed by 6 g of tetraethyl orthosilicate. The mixture was stirred and uniformly mixed. Ammonia was added dropwise to adjust the pH of the solution to 9.5. The mixture was heated to 45°C and stirred for 7 h. The mixture was centrifuged, washed, and dried to obtain silicon oxide-coated formaldehyde-melamine resin microspheres.
[0110] U3. Preparation of SiO2 / carbon nanotube hollow microspheres: 10 g of silicon oxide-coated formaldehyde-melamine resin microspheres were added to 150 mL of water, along with 0.15 g of ferric chloride. The mixture was stirred for 30 min, centrifuged, washed, dried, and calcined at 920°C under argon for 1 h to produce SiO2 / carbon nanotube hollow microspheres.
[0111] Preparation of U4.CaF2@SiO2 / carbon nanotube hollow microspheres: 10 g of SiO2 / carbon nanotube hollow microspheres were added to 200 mL of water, followed by 1.5 g of disodium EDTA. The mixture was stirred for 30 min. 4 g of calcium nitrate was added and adsorbed with stirring for 30 min. Then, 6 g of sodium fluoride was added. The mixture was hydrothermally reacted at 130°C for 15 h. The mixture was centrifuged, washed, and dried to obtain CaF2@SiO2 / carbon nanotube hollow microspheres.
[0112] U5. Preparation of modified CaF2@SiO2 / carbon nanotube hollow microspheres: 10 g of CaF2@SiO2 / carbon nanotube hollow microspheres were added to 20 mL of Tris-HCl solution (pH 9), 2.5 g of tannic acid was added, and the mixture was heated to 50°C and stirred for 4 h. The mixture was centrifuged, washed, and dried to obtain modified CaF2@SiO2 / carbon nanotube hollow microspheres.
[0113] U6. Preparation of rare earth-doped fluorescent nano-wear-resistant material: Add 10 g of modified CaF2@SiO2 / carbon nanotube hollow microspheres to 150 mL of water, add 1.5 g of cerium chloride and 1.2 g of yttrium nitrate, stir and react for 1.5 h, centrifuge, wash, and dry to obtain rare earth-doped fluorescent nano-wear-resistant material.
[0114] Comparative Preparation Example 6
[0115] Compared with Preparation Example 9, the difference is that step U5 is not performed.
[0116] The details are as follows:
[0117] U1. Preparation of formaldehyde-melamine resin microspheres: 10 g of formaldehyde solution and 200 mL of water were mixed, 2.5 g of melamine was added, the pH of the solution was adjusted to 5.2, and the reaction was stirred for 25 minutes. 0.15 g of cobalt chloride was added and the reaction was continued with stirring for 25 minutes. The mixture was centrifuged, washed, and dried to obtain formaldehyde-melamine resin microspheres.
[0118] U2. Silicon oxide coating: 10 g of formaldehyde-melamine resin microspheres were added to 200 mL of ethanol, followed by 6 g of tetraethyl orthosilicate. The mixture was stirred and uniformly mixed. Ammonia was added dropwise to adjust the pH of the solution to 9.5. The mixture was heated to 45°C and stirred for 7 h. The mixture was centrifuged, washed, and dried to obtain silicon oxide-coated formaldehyde-melamine resin microspheres.
[0119] U3. Preparation of SiO2 / carbon nanotube hollow microspheres: 10 g of silicon oxide-coated formaldehyde-melamine resin microspheres were added to 150 mL of water, along with 0.15 g of ferric chloride. The mixture was stirred for 30 min, centrifuged, washed, dried, and calcined at 920°C under argon for 1 h to produce SiO2 / carbon nanotube hollow microspheres.
[0120] Preparation of U4.CaF2@SiO2 / carbon nanotube hollow microspheres: 10 g of SiO2 / carbon nanotube hollow microspheres were added to 200 mL of water, followed by 1.5 g of disodium EDTA. The mixture was stirred for 30 min. 4 g of calcium nitrate was added and adsorbed with stirring for 30 min. Then, 6 g of sodium fluoride was added. The mixture was hydrothermally reacted at 130°C for 15 h. The mixture was centrifuged, washed, and dried to obtain CaF2@SiO2 / carbon nanotube hollow microspheres.
[0121] U5. Preparation of rare earth-doped fluorescent nano-wear-resistant material: 10g of CaF2@SiO2 / carbon nanotube hollow microspheres was added to 150mL of water, along with 1.5g of cerium chloride and 1.2g of yttrium nitrate. The mixture was stirred for 1.5h, centrifuged, washed, and dried to produce the rare earth-doped fluorescent nano-wear-resistant material.
[0122] Comparative Preparation Example 7
[0123] Compared with Preparation Example 9, the difference is that step U6 is not performed.
[0124] The details are as follows:
[0125] U1. Preparation of formaldehyde-melamine resin microspheres: 10 g of formaldehyde solution and 200 mL of water were mixed, 2.5 g of melamine was added, the pH of the solution was adjusted to 5.2, and the reaction was stirred for 25 minutes. 0.15 g of cobalt chloride was added and the reaction was continued with stirring for 25 minutes. The mixture was centrifuged, washed, and dried to obtain formaldehyde-melamine resin microspheres.
[0126] U2. Silicon oxide coating: 10 g of formaldehyde-melamine resin microspheres were added to 200 mL of ethanol, followed by 6 g of tetraethyl orthosilicate. The mixture was stirred and uniformly mixed. Ammonia was added dropwise to adjust the pH of the solution to 9.5. The mixture was heated to 45°C and stirred for 7 h. The mixture was centrifuged, washed, and dried to obtain silicon oxide-coated formaldehyde-melamine resin microspheres.
[0127] U3. Preparation of SiO2 / carbon nanotube hollow microspheres: 10 g of silicon oxide-coated formaldehyde-melamine resin microspheres were added to 150 mL of water, along with 0.15 g of ferric chloride. The mixture was stirred for 30 min, centrifuged, washed, dried, and calcined at 920°C under argon for 1 h to produce SiO2 / carbon nanotube hollow microspheres.
[0128] Preparation of U4.CaF2@SiO2 / carbon nanotube hollow microspheres: 10 g of SiO2 / carbon nanotube hollow microspheres were added to 200 mL of water, followed by 1.5 g of disodium EDTA. The mixture was stirred for 30 min. 4 g of calcium nitrate was added and adsorbed with stirring for 30 min. Then, 6 g of sodium fluoride was added. The mixture was hydrothermally reacted at 130°C for 15 h. The mixture was centrifuged, washed, and dried to obtain CaF2@SiO2 / carbon nanotube hollow microspheres.
[0129] U5. Preparation of modified CaF2@SiO2 / carbon nanotube hollow microspheres: 10 g of CaF2@SiO2 / carbon nanotube hollow microspheres were added to 20 mL of Tris-HCl solution with a pH of 9, 2.5 g of tannic acid was added, and the mixture was heated to 50°C and stirred for 4 h. The mixture was centrifuged, washed, and dried to obtain modified CaF2@SiO2 / carbon nanotube hollow microspheres.
[0130] Example 1
[0131] This embodiment provides a quick-setting hot-melt road marking paint.
[0132] Raw material composition (parts by weight): 100 parts of modified epoxy resin prepared in Preparation Example 1, 5 parts of triethylenediamine, 5 parts of titanium dioxide, 3 parts of self-repairing microcapsules prepared in Preparation Example 4, 2 parts of basalt fiber, 4 parts of rare earth-doped fluorescent nano-wear-resistant material prepared in Preparation Example 7, 3 parts of hollow glass microspheres, and 0.1 parts of rheological agent BYK-R-605.
[0133] The preparation method comprises the following steps:
[0134] The modified epoxy resin, titanium dioxide, self-repairing microcapsules, basalt fiber, rare earth doped fluorescent nano wear-resistant material and hollow glass microspheres were mixed evenly, rheological agent BYK-R-605 was added, stirred and mixed, and finally triethylenediamine was added and stirred to prepare a fast-setting hot-melt road marking paint.
[0135] Example 2
[0136] This embodiment provides a quick-setting hot-melt road marking paint.
[0137] Raw material composition (parts by weight): 110 parts of modified epoxy resin prepared in Preparation Example 2, 10 parts of tetraethylene trioxide, 10 parts of titanium dioxide, 5 parts of self-repairing microcapsules prepared in Preparation Example 5, 4 parts of basalt fiber, 6 parts of rare earth-doped fluorescent nano-wear-resistant material prepared in Preparation Example 8, 5 parts of hollow glass microspheres, and 0.2 parts of rheological agent BYK-R-605.
[0138] The preparation method comprises the following steps:
[0139] The modified epoxy resin, titanium dioxide, self-repairing microcapsules, basalt fiber, rare earth doped fluorescent nano wear-resistant material and hollow glass microspheres were mixed evenly, rheological agent BYK-R-605 was added, stirred and mixed, and finally tetraethylenetriamine was added and stirred to prepare a fast-setting hot-melt road marking paint.
[0140] Example 3
[0141] This embodiment provides a quick-setting hot-melt road marking paint.
[0142] Raw material composition (parts by weight): 105 parts of modified epoxy resin prepared in Preparation Example 3, 7 parts of triethylenediamine, 7 parts of titanium dioxide, 4 parts of self-repairing microcapsules prepared in Preparation Example 6, 3 parts of basalt fiber, 5 parts of rare earth-doped fluorescent nano-wear-resistant material prepared in Preparation Example 9, 4 parts of hollow glass microspheres, and 0.15 parts of rheological agent BYK-R-605.
[0143] The preparation method comprises the following steps:
[0144] The modified epoxy resin, titanium dioxide, self-repairing microcapsules, basalt fiber, rare earth doped fluorescent nano wear-resistant material and hollow glass microspheres were mixed evenly, rheological agent BYK-R-605 was added, stirred and mixed, and finally triethylenediamine was added and stirred to prepare a fast-setting hot-melt road marking paint.
[0145] Comparative Example 1
[0146] Compared with Example 3, the difference is that the modified epoxy resin is prepared by Comparative Preparation Example 1.
[0147] Comparative Example 2
[0148] Compared with Example 3, the difference is that the modified epoxy resin is prepared by Comparative Preparation Example 2.
[0149] Comparative Example 3
[0150] Compared with Example 3, the difference is that the self-repairing microcapsules are prepared by Comparative Preparation Example 3.
[0151] Comparative Example 4
[0152] Compared with Example 3, the difference is that the self-repairing microcapsules are prepared by Comparative Preparation Example 4.
[0153] Comparative Example 5
[0154] Compared with Example 3, the difference is that the self-repairing microcapsules are prepared by Comparative Preparation Example 5.
[0155] Comparative Example 6
[0156] Compared with Example 3, the difference is that the rare earth-doped fluorescent nano wear-resistant material is replaced by the product prepared in Comparative Preparation Example 6 of equal mass.
[0157] Comparative Example 7
[0158] Compared with Example 3, the difference is that the rare earth-doped fluorescent nano wear-resistant material is replaced by the product prepared in Comparative Preparation Example 7 of equal mass.
[0159] Comparative Example 8
[0160] Compared with Example 3, the difference is that no self-repairing microcapsules are added.
[0161] Comparative Example 9
[0162] Compared with Example 3, the difference is that no rare earth-doped fluorescent nano wear-resistant material is added.
[0163] Comparative Example 10
[0164] Compared with Example 3, the difference is that the modified epoxy resin is replaced by epoxy resin E51 of equal mass.
[0165] Test Example 1
[0166] The performance of the quick-setting hot-melt road marking paints prepared in Examples 1-3 or Comparative Examples 1-7 of the present invention was tested. The results are shown in Table 1.
[0167] Adhesion is tested according to the method of GB / T1720-2020;
[0168] Water resistance is tested according to the method of GB / T1733-1993;
[0169] Wear resistance is tested according to the method of GB / T1768-2006;
[0170] The stain resistance is tested according to GB / T 9780-2013 method;
[0171] The compressive strength test method is as follows: cast three 20mm×20mm×20mm coating compression test blocks, place them at room temperature for 24 hours and then perform a compression test. The accuracy of the electronic universal material testing machine shall not be less than 0.5 level, the preload shall be 10N, the loading speed shall be 30mm / min, and the compressive strength of different coatings shall be averaged.
[0172] The low-temperature crack resistance testing method is as follows: the marking paint is applied to artificial simulated asphalt pavement panels used for paint film testing to simulate road markings as test samples. Each paint sample is kept at -10°C for 4 hours and then placed at room temperature for 4 hours. This is considered a cycle. Repeat the cycle continuously and record the number of cycles when cracks appear.
[0173] Use a luminance tester to test the fluorescent luminance of the coating at room temperature (25°C).
[0174] Table 1
[0175]
[0176] It can be seen from the above table that the quick-setting hot-melt road marking paints prepared in Examples 1-3 of the present invention have good comprehensive properties.
[0177] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A quick-setting hot-melt road marking paint, characterized in that: The invention is prepared from the following raw materials in parts by weight: 100-110 parts of modified epoxy resin, 5-10 parts of curing agent, 5-10 parts of titanium dioxide, 3-5 parts of self-repairing microcapsules, 2-4 parts of basalt fiber, 4-6 parts of rare earth doped fluorescent nano wear-resistant material, 3-5 parts of hollow glass microspheres, and 0.1-0.2 parts of rheological agent.
2. The quick-setting hot-melt road marking paint according to claim 1, characterized in that: The preparation method of the modified epoxy resin is as follows: S1. The epoxy resin was added to ethanol, a composite silane coupling agent was added, the reaction was heated with stirring, and the solvent was removed under reduced pressure to obtain a silane coupling agent-modified epoxy resin; S2. Add the silane coupling agent-modified epoxy resin to acetone, add ethyl acrylate, methacrylic acid, and butyl acrylate, heat and stir to mix, add an initiator under the protection of an inert gas, keep warm and stir to react, add water to precipitate, filter, wash, and dry to obtain a modified epoxy resin.
3. The quick-setting hot-melt road marking paint according to claim 2, characterized in that: b. In step S1, the epoxy resin is E51, and the mass ratio of the epoxy resin to the composite silane coupling agent is 15-20:2-3. The composite silane coupling agent includes KH570 and KH602 in a mass ratio of 3-5:7-10. The temperature of the heating and stirring reaction is 40-50° C., and the time is 3-5 hours. In step S2, the mass ratio of the silane coupling agent-modified epoxy resin, ethyl acrylate, methacrylic acid, butyl acrylate, and initiator is 12-15:2-4:1-3:2-3:0.01-0.
015. The initiator is selected from at least one of sodium persulfate, potassium persulfate, and ammonium persulfate. The heating temperature is 50-60° C., and the heat-insulating and stirring reaction time is 4-6 hours.
4. The quick-setting hot-melt road marking paint according to claim 1, characterized in that: The preparation method of the self-repairing microcapsule is as follows: T1. The vapor phase SiO2 was added to ethanol, perfluorooctyl triethoxysilane and water were added, and the reaction was stirred to obtain SiO2-perfluorooctyl triethoxysilane emulsifier; T2. The vapor phase SiO2 was added to ethanol, dithiothiadiazole was added, silane coupling agent KH580 and water were added, and the reaction was stirred to obtain SiO2-dithiothiadiazole emulsifier; T3. The formaldehyde solution and triethanolamine were mixed, urea was added, the reaction was heated with stirring, melamine was added, and the reaction was kept warm to obtain a modified urea-formaldehyde resin prepolymer; T4. Evenly mix lauric acid, water, emulsifier, SiO2-perfluorooctyltriethoxysilane emulsifier, and SiO2-dimercaptothiadiazole emulsifier, add modified urea-formaldehyde resin prepolymer, adjust the pH value of the solution, heat and stir to react, and dry to obtain self-healing microcapsules.
5. The quick-setting hot-melt road marking paint according to claim 4, characterized in that: The mass ratio of the gaseous SiO2 and perfluorooctyltriethoxysilane in step T1 is 10:3-5, and the stirring reaction time is 10-12 hours; the mass ratio of the gaseous SiO2, dithiothiadiazole, and silane coupling agent KH580 in step T2 is 10:2-4:1-2, and the stirring reaction time is 10-12 hours; the mass ratio of the formaldehyde solution, triethanolamine, urea, and melamine in step T3 is 10:2-3:7-8:2-3, and the heating and stirring reaction temperature is 80-90 ℃, time is 0.5-1h, and the insulation reaction time is 0.5-1.5h; the mass ratio of lauric acid, water, emulsifier, SiO2-perfluorooctyltriethoxysilane emulsifier, SiO2-dimercaptothiadiazole emulsifier and modified urea-formaldehyde resin prepolymer in step T4 is 1-2:0.1-0.3:2-3:1-2:10, the pH value of the adjusted solution is 2-4, the temperature of the heating and stirring reaction is 40-50℃, the time is 2-4h, and the emulsifier is OP-10 or Tween-85.
6. The quick-setting hot-melt road marking paint according to claim 1, characterized in that: The preparation method of the rare earth doped fluorescent nano wear-resistant material is as follows: U1. Preparation of formaldehyde-melamine resin microspheres: Formaldehyde solution and water are uniformly mixed, melamine is added, the pH of the solution is adjusted, the reaction is stirred, a metal salt is added, the reaction is continued with stirring, centrifugation is performed, washing is performed, and drying is performed to obtain formaldehyde-melamine resin microspheres; U2. Silicon oxide coating: Formaldehyde - melamine resin microspheres were added to ethanol, alkyl orthosilicate was added, stirred and mixed, ammonia was added dropwise to adjust the pH of the solution, heated and stirred, centrifuged, washed, and dried to obtain silicon oxide-coated formaldehyde - melamine resin microspheres; U3. Preparation of SiO2 / carbon nanotube hollow microspheres: Silicon oxide-coated formaldehyde-melamine resin microspheres were added to water, followed by iron salt, stirred, centrifuged, washed, dried, and calcined to produce SiO2 / carbon nanotube hollow microspheres. Preparation of CaF2@SiO2 / carbon nanotube hollow microspheres: SiO2 / carbon nanotube hollow microspheres were added to water, followed by disodium EDTA, and stirred for reaction. Calcium salt was added and stirred for adsorption, followed by sodium fluoride. The mixture was hydrothermally reacted, centrifuged, washed, and dried to obtain CaF2@SiO2 / carbon nanotube hollow microspheres. U5. Preparation of modified CaF2@SiO2 / carbon nanotube hollow microspheres: CaF2@SiO2 / carbon nanotube hollow microspheres were added to a Tris-HCl solution, tannic acid was added, the reaction was heated with stirring, centrifuged, washed, and dried to obtain modified CaF2@SiO2 / carbon nanotube hollow microspheres; U6. Preparation of rare earth-doped fluorescent nano-wear-resistant material: Modified CaF2@SiO2 / carbon nanotube hollow microspheres were added to water, cerium chloride and yttrium nitrate were added, stirred, centrifuged, washed, and dried to obtain rare earth-doped fluorescent nano-wear-resistant material.
7. The quick-setting hot-melt road marking paint according to claim 6, characterized in that: In step U1, the mass ratio of the formaldehyde solution, melamine, and metal salt is 8-12:2-3:0.1-0.2, the metal salt is cobalt chloride, the pH value of the solution is adjusted to 5-5.5, and the stirring reaction is carried out for 20-30 minutes. In step U2, the mass ratio of the formaldehyde-melamine resin microspheres and alkyl orthosilicate is 10:5-7, the alkyl orthosilicate is methyl orthosilicate or ethyl orthosilicate, the pH value of the solution is adjusted to 9-10 by dripping ammonia water, the temperature of the heating and stirring reaction is 40-50° C., and the time is 6-8 hours. In step U3, the mass ratio of the silicon oxide-coated formaldehyde-melamine resin microspheres and iron salt is 100:2-3, the stirring reaction time is 20-40 minutes, and the calcination temperature is 900-950° C. and the time is 0.5-1.5 hours.
8. The quick-setting hot-melt road marking paint according to claim 6, characterized in that: In step U4, the mass ratio of SiO2 / carbon nanotube hollow microspheres, disodium EDTA, calcium salt, and sodium fluoride is 10:1-2:3-5:5-7, the temperature of the hydrothermal reaction is 120-140°C, and the time is 10-20 hours; in step U5, the mass ratio of CaF2@SiO2 / carbon nanotube hollow microspheres and tannic acid is 10:2-3, the temperature of the heating and stirring reaction is 45-55°C, and the time is 3-5 hours; in step U6, the mass ratio of modified CaF2@SiO2 / carbon nanotube hollow microspheres, cerium chloride, and yttrium nitrate is 10:1-2:0.6-1.5, and the stirring reaction time is 1-2 hours.
9. The quick-setting hot-melt road marking paint according to claim 1, characterized in that: The curing agent is triethylenediamine or tetraethylenetriamine; the rheological agent is rheological agent BYK-R-605.
10. A method for preparing the quick-setting hot-melt road marking paint according to any one of claims 1 to 9, characterized in that: The following steps are involved: The modified epoxy resin, titanium dioxide, self-repairing microcapsules, basalt fiber, rare earth doped fluorescent nano wear-resistant material and hollow glass microbeads are mixed evenly, a rheological agent is added, stirred and mixed, and finally a curing agent is added and the material is discharged to obtain a fast-setting hot-melt road marking paint.